Activity of Plasmin and Streptokinase-Activator on Substituted Arginine and Lysine Esters - Sherry, S; Alkjaersig, Norma; Fletcher, A. P (Thrombosis and Haemostasis, 1966)
Comparative studies have been made of the esterase activity of plasmin and the streptokinase-activator of plasminogen on a variety of substituted arginine and lysine esters. Human plasmin preparations derived by different methods of activation (spontaneous in glycerol, trypsin, streptokinase (SK) and urokinase) are similar in their esterase activity; this suggests that the molecular structure required for such esterase activity is similar for all of these human plasmins. Bovine plasmin, on the other hand, differs from human plasmin in its activity on several of the substrates studied (e.g., the methyl esters of benzoyl arginine and tosyl, acetyl and carbobenzoxy lysine), a finding which supports the view that molecular differences exist between the two animal plasmins. The streptokinase-activator hydrolyzes both arginine and lysine esters but the ratios of hydrolytic activity are distinct from those of plasmin and of other activators of plasminogen. The use of benzoyl arginine methyl ester as a substrate for the measurement of the esterase activity of the streptokinase-activator is described.